Clinical characteristics and outcomes of pregnant patients with COVID-19 at BPKIHS, a prospective study - Sah, Manoj K.; Pappu Rijal; Tulasha Basnet; Punita Yadav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Coronavirus disease (COVID-19) can vary in presentation, women present with a spectrum of clinical manifestations that range from mild symptoms and signs to severe illness, may require immediate advanced critical care support. Therefore, a hospital-based study was conducted to evaluate the effect of COVID-19 on maternal and perinatal outcomes of COVID-19 infected pregnant women. Methods: This was prospective descriptive study conducted at B. P. Koirala institute of health science. Total duration of study was one year from September 2020 to August 2021. This study was done in 70 pregnant ladies with confirmed SARS CoV2 infection. Different clinical presentation, mode of delivery, treatment given, need of oxygen, need of ICU admission, maternal outcomes, neonatal outcomes were observed. Result: The most common symptom was fever in 38 (54.2%) patients, followed by cough in 22 (31.5%) patients. Eighteen (25.71%) had mild degree of pneumonia with fall in oxygen saturation below 95% and required oxygen via face mask. Three patients (4.28%) develop sever pneumonia and required mechanical ventilation two (2.85%) had maternal mortality due to covid pneumonia. Most common mode of delivery was LSCS 21 (61.76%). Seven (10%) patients had preterm delivery. Conclusions: Most of the COVID-19 positive pregnant women remained asymptomatic or had mild infections. COVID-19 infections in late pregnancy might lead to an increased incidence of caesarean deliveries as observed in the present study. Adverse perinatal outcomes are mostly due to delayed presentation of patient to the hospital during COVID pandemic. High maternal mortality rate has been seen in present study. So proper intensive care is must for the management of such patient during pandemics. Also, efforts to limit exposure to COVID-19 of pregnant women should be strengthened for saving mother and child.